2009
DOI: 10.1111/j.1399-3054.2009.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

The gymnosperm Pinus pinea contains both AOX gene subfamilies, AOX1 and AOX2

Abstract: The gymnosperm Pinus pinea L. (stone pine) is a typical Mediterranean pine used for nuts and timber production, and as an ornamental around the world. Pine genomes are large in comparison to other species. The hypothesis that retrotransposons, such as gymny, made a large contribution to this alteration in genome size was recently confirmed. However, P. pinea is unique in other various aspects. P. pinea demonstrates a different pattern of gymny organization than other Pinus subgenera. Additionally, P. pinea has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…AOX1 and AOX2 genes can be discriminated by conserved nucleotide positions near important functional sites, such as the conserved cysteine in position CysI and the di‐iron‐binding sites. These sites have been recently highlighted by Costa et al (2009a) and Frederico et al (2009) (see arrows in Fig. 5).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…AOX1 and AOX2 genes can be discriminated by conserved nucleotide positions near important functional sites, such as the conserved cysteine in position CysI and the di‐iron‐binding sites. These sites have been recently highlighted by Costa et al (2009a) and Frederico et al (2009) (see arrows in Fig. 5).…”
Section: Discussionmentioning
confidence: 85%
“…Gray arrows indicate the position of a conserved prolin (P) and a conserved methionine (M) in AOX2 sub family identified by Costa et al (2009a). Black arrows indicate the positions of conserved methionine (M) and valine (V) in AOX2 sub family identified by Frederico et al (2009). Helical regions that are assumed to be involved in the formation of a hydroxo‐bridged binuclear iron center (Andersson and Nordlund 1999, Berthold et al 2000) are shown with overlines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Frederico et al 2009), and Physcomitrella patens (Neimanis et al 2013). The wide distribution of AOX in the plant kingdom raises the question of whether different plant species share common AOX gene structures and expression profiles.…”
Section: Communicated By Sureshkumar Balasubramanianmentioning
confidence: 99%